SISTEM INVENTORY MANAGEMENT UNTUK MENINGKATKAN VOLUME PENJUALAN DI TOKO HOKKY KRIAN - Fitriyani Gondowijoyo; Michael Ricky Sondak (Universitas Bunda Mulia, 2016)
This research aim for understanding the influence of inventory management system in increasing sales volume at Hokky Krian Store. The presence of inventory management system helping Hokky Krian Store increasing the sales volume. The population used in this research was the people working in inventory at Hokky Krian Store. The sample that being used in this research were the whole population because the population count is not much. Sample pulling technique used was non-probability sampling. This research using qualitative study case method. Data sources came from two sources, which is primary data including interview and observation, and secondary data from Hokky Krian Store financial report and literature from journals, books, and documents. Collecting method via interview with three research subjects, which is Hokky Store’s owner, Hokky Store’s supervisor, and an inventory management’s expert. Observation and documents analysis at Hokky Krian Store also used for collecting data in this research. Analysis technique used was Triangulation technique which is data validity checking technique that using outside data for checking and comparing the data. The result of this research concludes that good inventory management system will increase Hokky Krian Store sales volume. Therefore inventory should be done on a regular basis and the cost should be accounted whether inventory cost and production cost, controlling stock for bestseller item.Keywords: Inventory Management System, Sales Volume